2012
DOI: 10.1103/physreva.86.020701
|View full text |Cite
|
Sign up to set email alerts
|

Shape resonance spectra of lignin subunits

Abstract: We report integral cross sections for elastic electron scattering by the lignin subunits phenol, guaiacol, and p-coumaryl alcohol. Our calculations employed the Schwinger multichannel method with pseudopotentials and indicate three to four π * shape resonances for each of these systems, suggesting that low-energy electrons could efficiently transfer energy into the lignin matrix. We also discuss dissociation mechanisms based on the calculated cross sections, available experimental data, virtual orbital analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 29 publications
4
18
0
4
Order By: Relevance
“…As a consequence, we therefore foreshadow deriving integral vibrational excitation cross sections from the present data. In addition, the earlier elastic scattering SMC-SEP computation of de Oliveira et al 18 clearly identified three lower-lying (in terms of energy) shape resonances that impacted significantly on the energy dependence of that cross section. In all likelihood, those same resonances might well also decay into the open vibrational excitation channels.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…As a consequence, we therefore foreshadow deriving integral vibrational excitation cross sections from the present data. In addition, the earlier elastic scattering SMC-SEP computation of de Oliveira et al 18 clearly identified three lower-lying (in terms of energy) shape resonances that impacted significantly on the energy dependence of that cross section. In all likelihood, those same resonances might well also decay into the open vibrational excitation channels.…”
Section: Discussionmentioning
confidence: 96%
“…Considering the benzene vibrational excitation function spectrum and total cross section data in Kato et al, 33 there is no evidence for a higher-lying resonance at around 15 eV. On the other hand, in our earlier SMC calculation, at the static exchange plus polarisation (SEP) level, 18 a clear structure in the elastic integral cross section, between ∼10 and 20 eV, is found for phenol. This structure also persists in our more recent, more sophisticated, study from da Costa et al 21 and, even with the coarse energy grid of their measurements, is also apparent in the experimental total cross section results of da Costa et al 21 Hence, we believe that the observed discrepancy, between the present phenol CH stretch + combination mode at 90…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…This description can be summarized as (1) we have used 247 uncontracted Cartesian Gaussian functions for the description of target bound states and for the scattering calculations (CSFs basis of Eq. (4)), with s, p, and d types on the C and O atoms, and s and p types on the H atoms; (2) as usual, 14 a Hartree-Fock calculation was carried out for the ground state, giving a permanent dipole moment of 1.423 D against the experimental value of 1.224 D of Ref. 16; (3) following the same strategy as used in our recent electronethylene multichannel study 4 and as described in Ref.…”
Section: Computational Procedures Of the Present Application Of mentioning
confidence: 99%
“…Over the last few years, we have been interested in measuring intermediate-energy electron-impact cross sections, often for bands of composite vibrational quanta, in biomolecules such as water (H 2 O), 1,2 tetrahydrofuran (THF), [3][4][5][6] α-tetrahydrofurfuryl alcohol (THFA), 7 and pyrimidine (Py), 8 and for important products from the application of low-temperature plasmas 9,10 on biomass such as phenol 11,12 and furfural (this paper). There are several reasons for this, with one being to contribute to the creation of "complete" cross section data bases for those species.…”
Section: Introductionmentioning
confidence: 99%